2015
DOI: 10.1111/cmi.12534
|View full text |Cite
|
Sign up to set email alerts
|

Campylobacter jejuniouter membrane vesicle-associated proteolytic activity promotes bacterial invasion by mediating cleavage of intestinal epithelial cell E-cadherin and occludin

Abstract: Outer membrane vesicles (OMVs) play an important role in the pathogenicity of Gram-negative bacteria. Campylobacter jejuni produces OMVs that trigger IL-8, IL-6, hBD-3 and TNF-α responses from T84 intestinal epithelial cells and are cytotoxic to Caco-2 IECs and Galleria mellonella larvae. Proteomic analysis of 11168H OMVs identified the presence of three proteases, HtrA, Cj0511 and Cj1365c. In this study, 11168H OMVs were shown to possess proteolytic activity that was reduced by pretreatment with specific seri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
135
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(138 citation statements)
references
References 55 publications
3
135
0
Order By: Relevance
“…E-cadherin shedding can be induced by host proteases [30, 41] or by bacterial proteases, such as HtrA proteins [15, 27, 30]. To evaluate if HtrAs of S. Typhimurium, Y. enterocolitica , or P. mirabilis are expressed and capable of E-cadherin cleavage, we analyzed the expression of proteolytic active proteases by casein zymography in a first step.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…E-cadherin shedding can be induced by host proteases [30, 41] or by bacterial proteases, such as HtrA proteins [15, 27, 30]. To evaluate if HtrAs of S. Typhimurium, Y. enterocolitica , or P. mirabilis are expressed and capable of E-cadherin cleavage, we analyzed the expression of proteolytic active proteases by casein zymography in a first step.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, HtrA proteins are also implicated in the modulation of pathogen-host interaction by processing of surface-presented virulence factors or adhesins [14, 16, 17]. Another important function was observed for secreted or outer-membrane vesicle-associated HtrA from H. pylori and C. jejuni , which directly cleaves the extracellular domain of E-cadherin on host cells [15, 27, 29, 30]. HtrA-mediated E-cadherin cleavage opens intercellular adherens junctions allowing bacterial transmigration across the epithelial barrier [15, 29, 30, 33].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Campylobacter jejuni and its close relative Helicobacter pylori actively secrete HtrA proteins in the extracellular environment, where they target host cell factors [1921]. HtrA was also identified in outer membrane vesicles released by C. jejuni , H. pylori , Vibrio cholera , Chlamydia muridarum or Borrelia burgdorferi [2226]. Infection experiments with polarized cell monolayers in vitro suggested that H. pylori and C. jejuni HtrA can disrupt the epithelial barrier by opening cell-to-cell junctions.…”
Section: Introductionmentioning
confidence: 99%